Saint Mary of the Angels: Iconographic type of La Puebla de los Pardos, Costa Rica - Bonilla Soto, Luis Carlos (2026)
This article studies the construction of the iconographic type of Our Lady of the Angels of La Puebla de los Pardos, Costa Rica, from the 17th century to the present. The comparative of type iconographic method is applied to compare different representations of this title of Mary Virgin that exist in Costa Rica, with the aim to determine the attributes and forms of aesthetic composition that have allowed the consolidation of this Marian iconographic type, facilitating its reading and recognition by the Costa Rican population and defining it as a completely distinct representation from the artistic expressions venerated in churches under the title of Our Lady of the Angels in other countries around the world.